An Investigation into the Factors Affecting the Design of Nature-Compatible Recreational-Residential Complexes- Instance Analysis - Mirmahalleh, Seyyedeh Fatemeh Safavi; Samiei, Mohammad Mehdi Raeis (Journal of History Culture and Art Research, 2017)
Explaining tourism concepts, standards of recreational-residential complexes and the methods for accurate treating with nature, this paper tries to study the suitable instances of recreational-residential complexes and to adopt their positive aspects as a design strategy. SWOT matrix was built based on the weaknesses and strengths of the project site and design principles were derived by observing the extracted influential factors. Considering land topography, for example, different areas of buildings were shifted and combined with the nature. - Residential and public zones gained a nice view towards the nature by keeping their orientation and extending them in east-west direction - Service section connected more appropriately with residential and public areas - Sections which do not need extra light such as W.Cs, storages and installation rooms, were considered in a side of the building which was adjacent to soil - In residential section, rhythm was implemented in ceilings and windows - Golden values and proportions were used to design the plane and façade of the complex